FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI BATIK PADA INDUSTRI BATIK BUNGO DI KABUPATEN BUNGO PROVINSI JAMBI - Susanti, Ria Ana; Ernawati, Ernawati; Adriani, Adriani (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aim to describe how the tool, material, and labor in the batikindustry, and what are the factors thet influence the production of batik bungo.Thekind of this research is quantitative descriptive. It use saturated sampling. Datacollection did by using questionnaire with Likert scale, spread to all respondents thathave been passed validation and realibility test. version The result shows that theresults showed the tool and materials on the level achievement of the questionaire isvery good category (93,67%). Labor at the level achievement of the questionaire isvery good category (83,05%). Batik production at the level achievement of thequestionaire is very good category (86,5%). Based on regression testing, tool andmanpower positif effect on the production of batik, while material negatif effect.Factor influence the production of batik is a tool, material and labor the valueadjusted square (74,0%).keyword: batik production, jambi provincial district bungo